Adult-onset giant cervical cystic hygroma with pressure manifestations on aerodigestive tract, managed surgically: reporting of a rare case - Elshaar, Khaled (Ann R Coll Surg Engl, 2019)
Cystic hygroma is a benign congenital malformation of the lymphatic system that occurs in children younger than two years of age. Hygroma commonly presents in head and neck but can be present anywhere. It is rarely seen in adults. We report the case of a 28-year-old woman who presented with a huge painless right-sided cystic neck swelling of 11 months duration, associated with progressive dysphagia and difficulty in breathing when lying supine or on her left side. Clinically, the swelling occupied both right anterior and posterior triangles of her neck with impalpable right carotid pulsations. Computed tomography revealed a cystic mass lesion. The mass was excised totally through right supraclavicular incision, after identification of the great auricular, spinal accessory and phrenic nerves. Paraffin section confirmed the diagnosis of cystic hygroma. After an uneventful postoperative period the patient was discharged and has had no recurrence to date.